A Novel Blood Inflammatory Indicator for Predicting Deterioration Risk of Mild Traumatic Brain Injury - Ge, Xintong; Zhu, Luoyun; Li, Meimei; Li, Wenzhu; Chen, Fanglian; Li, Yongmei; Zhang, Jianning; Lei, Ping (Frontiers in Aging Neuroscience, 2022)
Mild traumatic brain injury (mTBI) has a relatively higher incidence in aging people due to walking problems. Cranial computed tomography and Magnetic Resonance Imaging provide the standard diagnosis tool to identify intracranial complications of patients with mTBI. However, it is still necessary to further explore blood biomarkers for evaluating the deterioration risk at the early-stage of mTBI, in order to improve medical decision-making in the emergency department. The activation of inflammatory response is one of the main pathological mechanisms leading to unfavorable outcomes of mTBI. As complete blood count (CBC) analysis is the most extensively applied laboratory test in practice, we extracted clinical data of 994 mTBI patients from two large clinical cohorts (MIMIC-IV and eICU-CRD), and selected inflammation-related indicators from CBC analysis to investigate their relationship with the deterioration after mTBI. The combinatorial indices neutrophil-to-lymphocyte ratio (NLR), red cell distribution width-to-platelet ratio (RPR), and NLR times RPR (NLTRP) were supposed to be potential risk predictors, and the data from above cohorts were integratively analyzed using our previously reported method named MeDICS. We found that NLR, RPR, and NLTRP levels were higher among deteriorated patients than non-deteriorated patients with mTBI. Besides, high NLTRP was associated with increased deterioration risk, with the odds ratio increasing from NLTRP of 1-2 (2.69, 1.48-4.89) to > 2 (4.44, 1.51-13.08), using NLTRP of 0-1 as the reference. NLTRP had a moderately good prognostic performance with an area under ROC Curve of 0.7554, and an incremental prediction value than both NLR and RPR, indicated by Integrated Discrimination Improvement index. The Decision Curve Analysis also showed greater clinical benefits of NLTRP than NLR, and RPR in a large range of threshold probability. Subgroup analysis further suggested that NLTRP is an independent risk factor for the deterioration after mTBI. In addition, in-vivo experiments confirmed the association between NLTRP and neural/systemic inflammatory response after mTBI, which emphasized the importance of controlling inflammation in clinical treatment. Consequently, NLTRP is a promising biomarker for the deterioration risk of mTBI. It can be used in resource-limited settings, thus being proposed as a routinely available tool at all levels of the medical system.